In situ synthesis of quasi-needle-like bimetallic organic frameworks on highly porous graphene scaffolds for efficient electrocatalytic water oxidation. Issue 21 (14th February 2020) - Khiarak, Behnam Nourmohammadi; Hasanzadeh, Mahdi; Mojaddami, Majdoddin; Shahriyar Far, Hossein; Simchi, Abdolreza
Abstract : We present enhanced electrocatalytic activity of three-dimensional graphene scaffolds by decoration with one-dimensional Co x Ni1− x MOF nanostructures (0 ≤ x ≤ 1). Abstract : We present enhanced electrocatalytic activity of three-dimensional graphene scaffolds by decoration with one-dimensional Co x Ni1− x MOF nanostructures (0 ≤ x ≤ 1). The decreased overpotential and fast kinetics of the oxygen evolution reaction as compared with the existing materials are shown. The developed bimetallic MOF/3DG composites have great potential to be used in electrocatalytic water oxidation.